What Drives Audit Quality in Food and Beverage Companies? - Ramadani, Maulia Putri; Setyorini, Dhyah (JAFFA, 2026)
This study aims to examine the effects of audit tenure, audit fees, and audit committees on audit quality in food and beverage companies listed on the Indonesia Stock Exchange (IDX) from 2019 to 2023. This quantitative study uses secondary data in the form of audited financial statements of food and beverage companies from 2019 to 2023, with a sample of 33 companies selected through purposive sampling and analyzed using logistic regression. This study contributes to providing empirical evidence regarding the factors that influence audit quality, particularly audit tenure, audit fees, and audit committees, in the relevant sector. The results indicate that audit tenure, audit fees, and audit committees each have no significant effect on audit quality in food and beverage companies listed on the IDX from 2019 to 2023. These findings contribute theoretically by enriching the literature on the determinants of audit quality, highlighting the inconsistencies in previous research results, and practically provide implications for management and regulators in evaluating the effectiveness of audit policies and oversight mechanisms.